Derrida contra Husserl : la crítica de la voz y el fenómeno a la teoría del signo de la primera investigación lógica de Husserl - Conde, Francisco (Investigaciones Fenomenológicas, 2007)
In this article the author tries to deconstruct the critic against Husserl´s analysis of the signs in the first logical investigation as it is exposed in Derridas ´s work Speech and Phenomena (1967). Derrida’s main critic is that the husserlian distinction between two kinds of signs – expressions (signs with signification) and indications- is unjustified and artificial. He also rejects the husserlian topic that sustains the ideality of significations and misinterprets the concept of meaning by understanding it as “the intention to say something”. The author of the article tries to show how Derrida manipulates the very strict husserlian notions by means of small but severe conceptual perversions that allow him to criticize without reason Husserls understanding of the meaning as built upon some conscious “forgetting” of the empiric side and of the indicative function of the expressions. The article begins with an exposition of some important points of the first logical investigation and then tries to show how Derrida manipulates them in his “approach” to the husserlian text.